Microbial Groundwater Sampling Protocol for Fecal‐Rich Environments. Issue 1 (5th June 2014) - Harter, Thomas; Watanabe, Naoko; Li, Xunde; Atwill, Edward R.; Samuels, William
Abstract Inherently, confined animal farming operations (CAFOs) and other intense fecal‐rich environments are potential sources of groundwater contamination by enteric pathogens. The ubiquity of microbial matter poses unique technical challenges in addition to economic constraints when sampling wells in such environments. In this paper, we evaluate a groundwater sampling protocol that relies on extended purging with a portable submersible stainless steel pump and Teflon® tubing as an alternative to equipment sterilization. The protocol allows for collecting a large number of samples quickly, relatively inexpensively, and under field conditions with limited access to capacity for sterilizing equipment. The protocol is tested on CAFO monitoring wells and considers three cross‐contamination sources: equipment, wellbore, and ambient air. For the assessment, we use Enterococcus, a ubiquitous fecal indicator bacterium (FIB), in laboratory and field tests with spiked and blank samples, and in an extensive, multi‐year field sampling campaign on 17 wells within 2 CAFOs. The assessment shows that extended purging can successfully control for equipment cross‐contamination, but also controls for significant contamination of the well‐head, within the well casing and within the immediate aquifer vicinity of the well‐screen. Importantly, our tests further indicate that Enterococcus is frequently entrained in water samples when exposed to ambient air at a CAFO during sample collection. Wellbore and air contamination pose separate challenges in the design of groundwater monitoring strategies on CAFOs that are not addressed by equipment sterilization, but require adequate QA/QC procedures and can be addressed by the proposed sampling strategy.